2001
DOI: 10.1063/1.1357442
|View full text |Cite
|
Sign up to set email alerts
|

A transversing connection between density functionals

Abstract: Accurate calculation and modeling of the adiabatic connection in density functional theoryWe identified a transversing physical connection between kinetic, exchange, and correlation functionals by using parameter-free ͑Pfree͒ exchange and one-parameter progressive ͑OP͒ correlation. On the basis of this connection, we investigated how the calculated energies and chemical properties depend on the shape of the functional in the Kohn-Sham scheme. We found that the fundamental conditions of the functionals are conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…This conclusion is also supported by the previous observation that calculated IPs are chiefly affected by the behavior of exchange functional in a low-density-high-gradient region where the long-range interaction governs. 62 We found that the lack of long-range exchange interaction may be responsible for the overstabilization problem of density functionals for electron configurations containing high-angular-momentum open-shell orbitals. This problem seems to be partly corrected by combining the Hartree-Fock exchange integral with the exchange functional, just like in the hybrid B3LYP functional.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is also supported by the previous observation that calculated IPs are chiefly affected by the behavior of exchange functional in a low-density-high-gradient region where the long-range interaction governs. 62 We found that the lack of long-range exchange interaction may be responsible for the overstabilization problem of density functionals for electron configurations containing high-angular-momentum open-shell orbitals. This problem seems to be partly corrected by combining the Hartree-Fock exchange integral with the exchange functional, just like in the hybrid B3LYP functional.…”
Section: Discussionmentioning
confidence: 99%
“…It is also suggested that calculated IPs are chiefly affected by the behavior of exchange functional in a low-density-high-gradient region where a long-range electron-electron interaction is dominant. 62 Following this argument, we may say that the relatively accurate s- …”
Section: The Outermost S and D Ionization Potentialsmentioning
confidence: 98%
“…The XC functionals based on LDA or the generalized‐gradient approximation (GGA) are used in the field of solid‐state physics. In isolated molecular systems, nonlocal exchange has been shown to be important . Hybrid functionals, which introduce HF exchange at a constant rate, are preferable in most applications.…”
Section: Introductionmentioning
confidence: 99%
“…31 Very recently, Hirao and co-workers arrived at ϭ 20 81 ϭ0.246 92, and suggested that the previous value of 10 81 might have been incorrect. 38 has also been empirically determined by fitting to certain set of the experimental data. For example, the popular Becke88 functional uses ϭ0.274 29.…”
Section: A the Termmentioning
confidence: 99%
“…11 However, there are alternative theoretical deductions of . [31][32][33][34][35][36][37][38] Based on wave-vector analysis, was determined as 10 81 ϭ0.123 46 in the slowly varying limit. 31 Very recently, Hirao and co-workers arrived at ϭ 20 81 ϭ0.246 92, and suggested that the previous value of 10 81 might have been incorrect.…”
Section: A the Termmentioning
confidence: 99%